Factors predicting post-traumatic seizure and epilepsy after traumatic brain injury- A retrospective study in tertiary care center of western Nepal (Journal of Brain and Spine Foundation Nepal, 2020)
Introduction: Posttraumatic seizures are the seizures that arise from traumatic brain injury and brain harm due to physical trauma. This study aims to study various clinic-demographic factors associated with post traumatic seizure in Western Nepal.Methods: A retrospective analytical study was carried out in a tertiary hospital of Nepal to determine factors associated with post traumatic seizures. Various parameters were tested for association with post traumatic seizure using student’s t test for quantitative and chi square or Fischer Exact test for categorical variables. All the variables showing significant association were subjected to binary logistic regression. P-value ≤0.05 was considered statistically significant.Results: There were 66 (21.02%) cases with post traumatic seizure in our study. Univariate analysis showed significant association of fall injury (p=0.004), loss of consciousness (p=0.001), post traumatic amnesia (p=0.012), severity of head injury (Glasgow coma scale) (p=0.011) and depressed fractures (p